A method for preparing a small-piece intercalation densified titanium carbide film
By introducing small-sized Ti3C2Tx nanosheets between the large-sized Ti3C2Tx nanosheets, and assembling the small-sized intercalated densified titanium carbide film by scraping the method, the problem of improving mechanical and electrical performance in the existing technology is solved, and high-performance titanium carbide is achieved Film preparation.
Patent Information
- Application Number
- CN202211435867.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-16
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-11-16
AI Technical Summary
The prior art is difficult to simultaneously improve the mechanical and electrical properties of large-size Ti3C2Tx nanosheet assembly films, and commonly used densification strategies will reduce electrical properties because crosslinking agents hinder electron transfer.
By evenly dispersing small-sized Ti3C2Tx nanosheets between the layers of large-sized Ti3C2Tx nanosheets at room temperature, the scraping method is used to assemble into a small-sized intercalated densified titanium carbide film to eliminate pores and improve performance.
The high density, tensile strength, Young's modulus, toughness and conductivity are achieved, and the interference of the use of crosslinking agents on electron transfer is avoided, and the intrinsic performance of the nanosheets is maintained to the maximum extent.
Smart Images

Figure CN115650235B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a small-piece intercalation densified titanium carbide film, and belongs to the field of nano composite material preparation. Background Art
[0002] Titanium carbide (Ti3C2T x ) nanosheets have excellent mechanical (Sci. Adv. 2018, 4, eaat0491.) and electrical (Appl. Phys. Lett. 2016, 108, 033102.) properties and have broad application prospects in flexible electronic devices and aerospace (Nat. Rev. Mater. 2017, 2, 16098.). Therefore, it is necessary to convert Ti3C2T x Nanosheets assembled into macroscopic high-performance Ti3C2T x Nanocomposite materials.
[0003] Typically, large-size Ti3C2T x Nanosheets help to enhance macroscopic Ti3C2T x Mechanical and electrical properties of thin films. For example, Razal et al. (Adv. Mater. 2020, 32, 2001093.) assembled large-scale Ti3C2T by blade coating. x Nanosheets (average lateral size of 10 μm) were prepared to produce high-strength and high-conductivity Ti3C2T x However, due to the pores between the large-sized nanosheets, when the thickness of the film increases from 0.94μm to 2.4μm, its tensile strength and conductivity decrease significantly. Therefore, it is necessary to develop a densification strategy to improve the performance of large-sized Ti3C2T x Recently, Cheng Qunfeng et al. (Science 2021, 374, 96.) conducted a study on the performance of thin films assembled from Ti3C2T x The introduction of sodium carboxymethyl cellulose and sodium tetraborate crosslinkers between the nanosheets effectively eliminated the pores and greatly improved the Ti3C2T x Mechanical properties of the composite film; however, the insulating crosslinker hinders the x The electron transfer between nanosheets, therefore, the prepared Ti3C2T x The electrical properties of the composite film are greatly reduced, limiting its practical application.
[0004] Therefore, it is necessary to develop novel densification strategies to simultaneously improve the density of large-sized Ti3C2T x The mechanical and electrical properties of the films assembled from nanosheets have not been studied so far. x Literature and patent reports on the preparation of densified titanium carbide films by nanosheet intercalation. Summary of the invention
[0005] The technology of the present invention solves the problem: overcomes the shortcomings of the prior art and provides a method for preparing a small-piece intercalated densified titanium carbide film. The prepared film has high density, excellent tensile strength, Young's modulus, toughness and electrical conductivity.
[0006] The present invention is realized by the following technical scheme: a method for preparing a small-piece intercalated densified titanium carbide film, firstly vortex-oscillating a large-size Ti3C2T x and small size Ti3C2T x Nanosheets blended with aqueous solution to make small-sized Ti3C2T x Nanosheets are uniformly dispersed in large Ti3C2T x Nanosheets; then the uniformly mixed aqueous solution is assembled into small intercalated densified titanium carbide (IDM) films by a doctor blade coating method. The specific implementation steps are as follows:
[0007] A method for preparing a small-piece intercalation densified titanium carbide film comprises the following steps:
[0008] (1) The first size titanium carbide (Ti3C2T) was prepared by stirring and ultrasonic method at room temperature. x ) nanosheets and the second size Ti3C2T x The nanosheets are respectively prepared into uniform first size Ti3C2T x Aqueous solution and second size Ti3C2T x aqueous solution; the average surface area of the first size titanium carbide nanosheets is greater than that of the second size Ti3C2T x Average surface area of nanosheets;
[0009] (2) The first size Ti3C2T obtained in step (1) x Aqueous solution and second size Ti3C2T x The aqueous solution was mixed and vortexed to make the second size Ti3C2T x Nanosheets are uniformly dispersed in the first size Ti3C2T x Between the nanosheet layers, a uniformly mixed aqueous solution is obtained;
[0010] (3) The mixed aqueous solution is subjected to vacuum degassing, and then assembled into small pieces of intercalated densified titanium carbide (IDM) films by a doctor blade coating method.
[0011] Wherein, the first size titanium carbide (Ti3C2T x ) nanosheets are large-sized Ti3C2T x Nanosheets; the second size Ti3C2T x Nanosheets are small-sized Ti3C2T x Nanosheets.
[0012] Furthermore, the first size Ti3C2T x The average surface area of the nanosheets is 25 to 900 μm 2 For example, the first size Ti3C2T x The average surface area of the nanosheets is 25, 50, 100, 150, 160, 169, 200, 250, 300, 350, 400, 450, 500, 550, 600, 700, 800 or 900 μm 2 .
[0013] Furthermore, the second size Ti3C2T x The average surface area of the nanosheets is 0.01 to 1 μm 2 For example, the second size Ti3C2T x The average surface area of the nanosheets is 0.01, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.9 or 1 μm 2 .
[0014] Furthermore, in step (1), the large-sized Ti3C2T x The aqueous solution contains large-sized Ti3C2T x In the step (1), the small size Ti3C2T x The aqueous solution contains small-sized Ti3C2T x Nanosheets.
[0015] Furthermore, in step (1), the large-sized Ti3C2T x Nanosheets and small-sized Ti3C2T x The average surface area ratio of the nanosheets is greater than 400.
[0016] Furthermore, in step (1), the large-sized Ti3C2T x Aqueous solution and small size Ti3C2T x The concentration of the aqueous solution is 15 to 60 mg / mL.
[0017] Furthermore, in the step (1), the stirring time is 10 to 20 minutes, the ultrasonic time is 0.5 to 1 minute, and the ultrasonic power in the ice water bath is 50 to 70 W, so that the Ti3C2T x In the case of nanosheet structure, uniformly dispersed Ti3C2T x Nanosheets.
[0018] Furthermore, in step (2), the large-sized Ti3C2T xNanosheets and small-sized Ti3C2T x The mass ratio of the nanosheets is 3 to 20. For example, in step (2), the large-sized Ti3C2T x Nanosheets and small-sized Ti3C2T x The mass ratio of the nanosheets is 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20. x The nanosheet content is too low to effectively fill the large Ti3C2T x Nanosheet interlayer pores, while small size Ti3C2T x Too high a content of nanosheets will interfere with the large-size Ti3C2T x The ordered arrangement structure of nanosheets is not conducive to improving the performance of IDM films. In order to better optimize the density and performance of IDM films, large-size Ti3C2T x Nanosheets and small-sized Ti3C2T x The mass ratios of the nanosheets were selected as 95:5, 90:10, 85:15, and 80:20, respectively, and the corresponding four IDM films were labeled as IDM-I, IDM-II, IDM-III, and IDM-IV, respectively.
[0019] Furthermore, in the step (2), the vortex oscillation speed is 1000-2000 rpm, and the time is 2-3 min, which not only makes the small-sized Ti3C2T x Nanosheets are uniformly dispersed in large Ti3C2T x Nanosheets, and ensure Ti3C2T x The nanosheet structure does not break.
[0020] Furthermore, in the step (3), the process of vacuum degassing is to place the mixed aqueous solution in a closed dryer, evacuate to a vacuum degree of 2000-4000 Pa, and maintain this vacuum degree for 3-5 minutes, and then release the air, and repeat the above vacuuming and releasing process 7-10 times to completely remove the bubbles in the mixed aqueous solution.
[0021] Furthermore, in the step (3), a scraping method is adopted, and the specific implementation process thereof includes:
[0022] (1) dripping the mixed aqueous solution after vacuum evacuation of bubbles onto the substrate surface of the coating machine;
[0023] (2) adjusting the distance between the scraper and the substrate to 0.2 to 3 mm, and then starting the coating machine for scraping, with the scraper speed being 2 to 10 cm / s;
[0024] (3) The temperature of the substrate is adjusted to 35-45° C. and heated for 1-2 h to dry the spread mixed aqueous solution. When the water is removed, an IDM film is obtained.
[0025] In the step (3), the thickness of the obtained IDM film is 0.5 to 20 μm. For example, the thickness of the obtained IDM film is 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 μm.
[0026] The principle of the invention is to combine small-sized Ti3C2T x Nanosheets introduce large-size Ti3C2T x The interlayer of nanosheets effectively fills large-sized Ti3C2T x The pores between the nanosheets enable Ti3C2T x Densification of the film and improvement of Ti3C2T x Mechanical and electrical properties of the films.
[0027] Compared with the existing densified Ti3C2T x Compared with the thin film technology, the characteristics and advantages of the present invention are:
[0028] (1) Small size Ti3C2T x Nanosheets can be obtained by crushing large-sized Ti3C2T x The nanosheets are directly obtained, and no additional cross-linking agent of other components is required in the preparation process, which is conducive to making the prepared Ti3C2T x The film maintains Ti3C2T to the maximum extent x The intrinsic properties of nanosheets;
[0029] (2) Small size Ti3C2T x Nanosheets are filled in large Ti3C2T x The interlayer of nanosheets not only eliminates the pores, but also acts as a medium for electron transport and stress transfer, while improving the performance of Ti3C2T x Mechanical and electrical properties of the films.
[0030] Therefore, the IDM film prepared by the present invention has high density (86.7% to 92.2%), high tensile strength (223 to 409 MPa), high Young's modulus (12.2 to 14.5 GPa), high toughness (2.57 to 4.12 MJ / m 3 ), high conductivity (9998~10865S / cm). BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Indicates A-large size Ti3C2T xTi3C2T nanosheets assembled x Scanning electron microscope (SEM) photos of the ion beam cut sections of (LM) film and B-IDM-II film. Compared with the LM film, the IDM-II film has a denser structure.
[0032] Figure 2 A-tensile stress-strain curves and B-electrical conductivity of LM and IDM-II films are shown. Compared with LM film, IDM-II film has higher tensile strength, Young's modulus, toughness and electrical conductivity. DETAILED DESCRIPTION
[0033] The present invention is described in detail below through specific embodiments. However, the following embodiments are limited to explaining the present invention, and the protection scope of the present invention should include the entire contents of the claims, and through the description of the following embodiments, those skilled in the art can fully implement the entire contents of the claims of the present invention.
[0034] The parameter testing method of the following embodiments of the present invention is as follows:
[0035] The tensile strength, toughness and Young's modulus test method includes the following steps: (1) first cut the film sample into a 3×10mm rectangular sample strip; (2) then use epoxy resin to bond the sample strip to a paper frame with a hollow center, wherein the size of the paper frame is 15×25mm, the size of the central hollow area is 5×10mm, and the sample strip is symmetrically fixed on the paper frame across the center of the hollow area, and the 10mm side of the sample strip, the 5mm side of the hollow area and the 25mm side of the paper frame are parallel; (3) after the epoxy resin is cured, fix the paper frame on the fixture of the Sansi Zongheng UTM4103 universal mechanical testing machine, wherein the span is 5mm; (4) then use scissors to cut off the two side frames of the hollow area of the paper frame, and start the universal Mechanical testing machine software is used to perform tensile mechanical property tests to obtain the stress-strain curve of the sample strip, wherein the tensile rate is 1 mm / min, and the cross-sectional area of the sample strip is obtained by multiplying the width (3 mm) and thickness (the thickness of the sample strip at 3 to 5 different positions on the cross section is characterized by a JEOL-7500F scanning electron microscope, and then the average value is calculated). The tensile stress at the fracture point of the stress-strain curve, the integral area, and the slope of the linear range of the initial elastic deformation are the tensile strength, toughness, and Young's modulus of the sample strip, respectively; (5) 3 to 5 sample strips are tested for each film sample, and their tensile strength, toughness, and Young's modulus are the average values of the tensile strength, toughness, and Young's modulus of the corresponding 3 to 5 sample strips, respectively.
[0036] The conductivity test method includes the following steps: (1) firstly cutting the film sample into a rectangular sample strip of 2×30 mm; (2) then fixing the two ends of the sample strip on the two electrodes of the Keithley2400 digital source meter with conductive silver paste; (3) after the conductive silver paste is solidified, turning on the Keithley2400 digital source meter, reading the resistance, and then calculating the conductivity of the sample strip according to the length and cross-sectional area of the sample strip; (4) testing 3 to 5 sample strips for each film sample, and the conductivity thereof is the average value of the conductivity of the corresponding 3 to 5 sample strips.
[0037] The density test method includes the following steps: (1) cutting the film sample into a 50×50 mm square sample strip; (2) using a Sartorius BT125D electronic microbalance to weigh the mass of the sample strip, using a JEOL-7500F scanning electron microscope to characterize the thickness of 3 to 5 different positions on the cross section of the sample strip, and then taking the average value to obtain the thickness of the sample strip; (3) dividing the mass by the thickness and the surface area to obtain the actual density of the sample strip, and then dividing the actual density of the sample strip by the theoretical density of the corresponding film to obtain the density of the film sample, where the large-size Ti3C2T x and small size Ti3C2T x The theoretical density of the nanosheets was obtained by the following method: First, an X-ray photoelectron spectrometer (ESCALab220i-XL) was used to characterize the large-size Ti3C2T x and small size Ti3C2T x The elemental composition of the nanosheets was then x Nanosheets are considered as Al in Ti3AlC2 being replaced by T x After substitution, the theoretical density of Ti3AlC2 (4.24 g / cm 3 ) and Ti3C2T x The relative molecular weight and unit cell volume of Ti3AlC2 can be calculated to obtain the large-size Ti3C2T x and small size Ti3C2T x Theoretical density of nanosheets. Furthermore, combined with large-size Ti3C2T x and small size Ti3C2T x The mass ratio of the nanosheets allows the theoretical density of each film to be calculated.
[0038] The preparation methods of some raw materials used in the following examples of the present invention are as follows:
[0039] Large size Ti3C2T xThe preparation method of the nanosheets comprises the following steps: (1) taking 15 mL of concentrated hydrochloric acid (concentration of 12 mol / L) into a polytetrafluoroethylene reagent bottle, and then adding 5 mL of deionized water thereto to obtain a diluted hydrochloric acid solution; (2) weighing 1.6 g of lithium fluoride powder, adding it to the diluted hydrochloric acid solution under continuous stirring, and continuing to stir for 5 minutes to obtain an etching solution; (3) weighing 1.0 g of titanium aluminum carbide (Ti3AlC2) powder, adding it to the etching solution under continuous stirring, and then sealing the polytetrafluoroethylene reagent bottle, placing it in a water bath at 50°C, stirring at a constant temperature, and reacting for 30 hours; (4) evenly placing the mixed solution after the reaction into 4 50 mL centrifuge tubes, and then Then, 30 mL of deionized water was added to each centrifuge tube, and the mixture was centrifuged at 3500 rpm for 5 min. The supernatant was removed, and the above process of adding deionized water, centrifuging, and removing the supernatant was repeated 6 to 8 times until the supernatant turned dark green and the lower layer precipitated into a paste-like slurry; (5) 30 mL of deionized water was added to the above paste-like slurry precipitate in each centrifuge tube, and then vortexed (2000 rpm) for 3 min, and then centrifuged at 1500 rpm for 20 min, and the supernatant was collected; (6) The supernatant collected in step (5) was further centrifuged at 4000 rpm for 20 min, and the precipitate after centrifugation was collected. The precipitate was vacuum dried to obtain large-sized Ti3C2T x Nanosheet powder, with an average surface area of 169 μm 2 .
[0040] Small size Ti3C2T xThe preparation method of the nanosheet comprises the following steps: (1) taking 15 mL of concentrated hydrochloric acid (concentration of 12 mol / L) into a polytetrafluoroethylene reagent bottle, and then adding 5 mL of deionized water thereto to obtain a diluted hydrochloric acid solution; (2) weighing 1.6 g of lithium fluoride powder, adding it to the diluted hydrochloric acid solution under continuous stirring, and continuing to stir for 5 minutes to obtain an etching solution; (3) weighing 1.0 g of titanium aluminum carbide (Ti3AlC2) powder, adding it to the etching solution under continuous stirring, and then sealing the polytetrafluoroethylene reagent bottle, and placing it in a water bath at 50°C for constant temperature stirring and reaction for 30 hours; (4) evenly placing the mixed solution after the reaction into 4 50 mL centrifuge tubes, and then adding 30 mL of deionized water into each centrifuge tube; water, centrifuged at 3500 rpm for 5 min, removed the supernatant, repeated the above process of adding deionized water, centrifuging, and removing the supernatant 6 to 8 times until the supernatant appears dark green and the lower layer precipitates into a paste slurry; (5) added 30 mL of deionized water to the above paste slurry precipitate in each centrifuge tube, and then vortexed (2000 rpm) for 3 min, and then centrifuged at 1500 rpm for 20 min, and the supernatant was collected; (6) under the condition of continuous nitrogen flow, the supernatant collected in step (5) was placed in an ice bath and ultrasonicated (100 W) for 2.5 h, and then the obtained solution was centrifuged at 9500 rpm for 20 min, and the precipitate after centrifugation was collected, and the precipitate was vacuum dried to obtain small-sized Ti3C2T x Nanosheet powder, with an average surface area of 0.25 μm 2 .
[0041] Example 1
[0042] Prepare 30 mg / mL large-sized Ti3C2T x Nanosheets (average surface area 169 μm 2 ) Aqueous solution: weigh 150 mg of large-sized Ti3C2T x The nanosheets were added into 5 mL of deionized water, mechanically stirred for 15 min, and then dispersed in an ice-water bath with ultrasound (60 W) for 0.75 min. The same procedure was used to prepare small-sized Ti3C2T x Nanosheets were formulated into small-sized Ti3C2T3O3 nanosheets at 30 mg / mL. x Nanosheets (average surface area 0.25 μm 2 ) aqueous solution; then the large size Ti3C2T x Aqueous solution and small size Ti3C2T xThe aqueous solutions were mixed in a volume ratio of 95:5; after vortex oscillation (1500rpm) for 2.5min, the uniformly mixed aqueous solution was placed in a closed desiccator, evacuated to a vacuum degree of 3000Pa, and maintained at this vacuum degree for 4min, and then released, and the above-mentioned vacuuming and releasing process was repeated 8 times to completely remove the bubbles in the mixed aqueous solution; then the mixed aqueous solution was slowly dripped onto the substrate surface of the coating machine close to the scraper, and the distance between the scraper and the substrate was adjusted to 0.5mm, the coating machine was started, and the scraper was applied at a speed of 5cm / s; finally, the temperature of the substrate was adjusted to 40℃ and heated for 1h to obtain a small piece of intercalated densified titanium carbide (IDM-I) film, the thickness of the IDM-I film was 2.7±0.1μm.
[0043] Density tests showed that the density of the IDM-I film was 86.7%. Mechanical and electrical property tests were performed on 3 to 5 sample strips, and the results showed that its tensile strength was 243±12MPa, Young's modulus was 12.2±1.6GPa, and toughness was 3.16±0.12MJ / m 3 , the conductivity is 10340±159S / cm.
[0044] Example 2
[0045] Prepare 30 mg / mL large-sized Ti3C2T x Nanosheets (average surface area 169 μm 2 ) Aqueous solution: weigh 150 mg of large-sized Ti3C2T x The nanosheets were added into 5 mL of deionized water, mechanically stirred for 15 min, and then dispersed in an ice-water bath with ultrasound (60 W) for 0.75 min. The same procedure was used to prepare small-sized Ti3C2T x Nanosheets were formulated into small-sized Ti3C2T3O3 nanosheets at 30 mg / mL. x Nanosheets (average surface area 0.25 μm 2 ) aqueous solution; then the large size Ti3C2T x Aqueous solution and small size Ti3C2T xThe aqueous solutions were mixed in a volume ratio of 90:10; after vortex oscillation (1500rpm) for 2.5min, the uniformly mixed aqueous solution was placed in a closed desiccator, evacuated to a vacuum degree of 3000Pa, and maintained at this vacuum degree for 4min, and then released, and the above-mentioned vacuuming and releasing process was repeated 8 times to completely remove the bubbles in the mixed aqueous solution; then the mixed aqueous solution was slowly dripped onto the substrate surface of the coating machine close to the scraper, and the distance between the scraper and the substrate was adjusted to 0.5mm, the coating machine was started, and the scraper was applied at a speed of 5cm / s; finally, the temperature of the substrate was adjusted to 40℃ and heated for 1h to obtain a small piece of intercalated densified titanium carbide (IDM-II) film, the thickness of the IDM-II film was 2.8±0.2μm.
[0046] Density tests show that the density of the IDM-II film is 90.9%. Mechanical and electrical property tests were performed on 3 to 5 sample strips, and the results showed that its tensile strength was 409±26MPa, Young's modulus was 13.7±1.0GPa, and toughness was 4.12±0.56MJ / m 3 , the conductivity is 10865±203S / cm.
[0047] Example 3
[0048] Prepare 30 mg / mL large-sized Ti3C2T x Nanosheets (average surface area 169 μm 2 ) Aqueous solution: weigh 150 mg of large-sized Ti3C2T x The nanosheets were added into 5 mL of deionized water, mechanically stirred for 15 min, and then dispersed in an ice-water bath with ultrasound (60 W) for 0.75 min. The same procedure was used to prepare small-sized Ti3C2T x Nanosheets were formulated into small-sized Ti3C2T3O3 nanosheets at 30 mg / mL. x Nanosheets (average surface area 0.25 μm 2 ) aqueous solution; then the large size Ti3C2T x Aqueous solution and small size Ti3C2T xThe aqueous solutions were mixed in a volume ratio of 85:15; after vortex oscillation (1500rpm) for 2.5min, the uniformly mixed aqueous solution was placed in a closed desiccator, evacuated to a vacuum degree of 3000Pa, and maintained at this vacuum degree for 4min, and then released, and the above-mentioned vacuuming and releasing process was repeated 8 times to completely remove the bubbles in the mixed aqueous solution; then the mixed aqueous solution was slowly dripped onto the substrate surface of the coating machine close to the scraper, and the distance between the scraper and the substrate was adjusted to 0.5mm, the coating machine was started, and the scraper was applied at a speed of 5cm / s; finally, the temperature of the substrate was adjusted to 40℃ and heated for 1h to obtain a small piece of intercalated densified titanium carbide (IDM-III) film, the thickness of the IDM-III film was 2.7±0.2μm.
[0049] Density tests show that the density of the IDM-III film is 91.5%. Mechanical and electrical property tests were performed on 3 to 5 sample strips, and the results showed that its tensile strength was 328±21MPa, Young's modulus was 14.0±1.3GPa, and toughness was 3.42±0.38MJ / m 3 , the conductivity is 10422±185S / cm.
[0050] Example 4
[0051] Prepare 30 mg / mL large-sized Ti3C2T x Nanosheets (average surface area 169 μm 2 ) Aqueous solution: weigh 150 mg of large-sized Ti3C2T x The nanosheets were added into 5 mL of deionized water, mechanically stirred for 15 min, and then dispersed in an ice-water bath with ultrasound (60 W) for 0.75 min. The same procedure was used to prepare small-sized Ti3C2T x Nanosheets were formulated into small-sized Ti3C2T3O3 nanosheets at 30 mg / mL. x Nanosheets (average surface area 0.25 μm 2 ) aqueous solution; then the large size Ti3C2T x Aqueous solution and small size Ti3C2T xThe aqueous solutions were mixed in a volume ratio of 80:20; after vortex oscillation (1500rpm) for 2.5min, the uniformly mixed aqueous solution was placed in a closed desiccator, evacuated to a vacuum degree of 3000Pa, and maintained at this vacuum degree for 4min, and then released, and the above-mentioned vacuuming and releasing process was repeated 8 times to completely remove the bubbles in the mixed aqueous solution; then the mixed aqueous solution was slowly dripped onto the substrate surface of the coating machine close to the scraper, and the distance between the scraper and the substrate was adjusted to 0.5mm, the coating machine was started, and the scraper was applied at a speed of 5cm / s; finally, the temperature of the substrate was adjusted to 40℃ and heated for 1h to obtain a small piece of intercalated densified titanium carbide (IDM-IV) film, the thickness of the IDM-IV film was 2.6±0.1μm.
[0052] Density tests show that the density of the IDM-IV film is 92.2%. Mechanical and electrical property tests were performed on 3 to 5 sample strips, and the results showed that its tensile strength was 223±19MPa, Young's modulus was 14.5±1.1GPa, and toughness was 2.57±0.30MJ / m 3 , the electrical conductivity is 9998±108S / cm.
[0053] Comparative Example 1
[0054] Compared with Example 1, except that no small-sized Ti3C2T x Except for the nanosheet aqueous solution, the other conditions were the same. The thickness of the prepared titanium carbide film (LM film) was 2.7±0.1μm, the density was 83.9%, the tensile strength was 185±6MPa, the Young's modulus was 9.5±0.7GPa, and the toughness was 2.36±0.02MJ / m 3 , the conductivity is 9822±133S / cm. Figure 1 A-shows the large-sized Ti3C2T prepared in Comparative Example 1 x Ti3C2T nanosheets assembled x (LM) Scanning electron microscope (SEM) image of the ion beam cut cross section of the film. Figure 1 B- is a scanning electron microscope (SEM) photograph of the ion beam cut section of the IDM-II film prepared in Example 2. Compared with the LM film, the IDM-II film has a denser structure. Figure 2 A-tensile stress-strain curve and B-conductivity of LM and IDM-II films are shown. Compared with LM film, IDM-II film has higher tensile strength, Young's modulus, toughness and conductivity. x There are many pores between the nanosheets, and the Ti3C2T x The mechanical and electrical properties of the film are poor; xNanosheets inserted into large Ti3C2T x After the nanosheets are interlayered, the pores can be effectively eliminated and the Ti3C2T x Mechanical and electrical properties of the films.
[0055] In summary, the small intercalated densified titanium carbide film obtained by the present invention has high density (90.9%), high tensile strength (409MPa), high Young's modulus (13.7GPa), high toughness (4.12MJ / m 3 ) and high electrical conductivity (10865S / cm). This kind of densified and high-performance titanium carbide film has a wide range of applications in flexible electronic devices and aerospace.
[0056] It should be noted that, according to the above-mentioned embodiments of the present invention, those skilled in the art can fully implement the full scope of the independent claims and dependent rights of the present invention, and the implementation process and method are the same as the above-mentioned embodiments; and the parts not elaborated in detail in the present invention belong to the well-known technology in the field.
[0057] The above descriptions are only some specific implementation methods of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any person familiar with the art within the technical scope disclosed in the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing a small-piece intercalation densified titanium carbide film, characterized in that: The steps include: (1) At room temperature, the first size Ti3C2T x Nanosheets and the second size Ti3C2T x The nanosheets are respectively prepared into uniform first size Ti3C2T x Aqueous solution and second size Ti3C2T x Aqueous solution; First size Ti3C2T x Aqueous solution and second size Ti3C2T x The concentration of aqueous solution is 15~60 mg / mL; the first size Ti3C2T x The average surface area of the nanosheets is 150~900 μm 2 ; Second size Ti3C2T x The average surface area of the nanosheets is 0.2~1 μm 2 ; First size Ti3C2T x Nanosheets and the second size Ti3C2T x The average surface area ratio of the nanosheets is greater than 400; (2) The first size Ti3C2T obtained in step (1) x Aqueous solution and second size Ti3C2T x The aqueous solution was mixed and vortexed to make the second size Ti3C2T x Nanosheets are uniformly dispersed in the first size Ti3C2T x Between the nanosheets, a uniform mixed aqueous solution is obtained; the first size Ti3C2T x Nanosheets and the second size Ti3C2T x The mass ratio of nanosheets is 3 to 20; (3) vacuum-degassing the mixed aqueous solution obtained in step (2), and then assembling it into small pieces of intercalated densified titanium carbide films by a doctor blade coating method; In the step (3), the specific implementation process of assembling the mixed aqueous solution after vacuum degassing into an IDM film by a scraping method includes: (31) dripping the mixed aqueous solution after vacuum degassing onto the substrate surface of the coating machine; (32) Adjust the distance between the scraper and the substrate to 0.2–3 mm, then start the coating machine for scraping, with the scraper speed at 2–10 cm / s; (33) The substrate temperature is adjusted to 35–45 °C and heated for 1–2 h to dry the spread mixed aqueous solution. When the water is removed, a small piece of intercalated densified titanium carbide film is obtained. In the step (1), the stirring time is 10 to 20 min, the ultrasonic time is 0.5 to 1 min, the ultrasonic power is 50 to 70 W, and the ultrasonication is carried out in an ice water bath; In the step (2), the vortex oscillation speed is 1000-2000 rpm, and the time is 2-3 min. In the step (3), the thickness of the obtained small intercalated densified titanium carbide film is 0.5-20 μm.
2. The method for preparing a small-piece intercalation densified titanium carbide film according to claim 1, characterized in that: In the step (3), the vacuum degassing process is to place the mixed aqueous solution in a closed desiccator, evacuate to a vacuum degree of 2000-4000 Pa, and maintain this vacuum degree for 3-5 minutes, and then release the air, and repeat the above vacuuming and releasing process 7-10 times.
